Co-Occurrence of Violence on the Severity of Abuse in Intimate Relationships - Ouellet, Frédéric (Journal of interpersonal violence, 2022)
Several empirical studies have shown that women who experience violence in intimate personal relationships (IPV) commonly experience more than one form of violence. While it is recognized that individual trajectories of IPV vary over time, little is known about the temporal dynamics of this co-occurrence or its consequences. This study describes the different forms of violence experienced by women and looks at whether it is possible to predict when severe violence (physical and sexual) is most likely to occur. Data in the study comes from interviews with 70 women who had been victims of intimate partner violence. The life history calendar method was used to facilitate identifying kinds and levels of violence and the month in which violence took place. Individual victimization trajectories were found to be heterogenous and likely to change in the short term. The women in our sample experienced more than one form of intimate partner violence and co-occurrence of different forms of violence was common in individual trajectories. The characteristics of the kind of violence experienced were important in understanding the temporal aspects of acts of severe violence. The increased knowledge about patterns of violence provided by these results should help to develop better ways to intervene to prevent such events.